RESULTS OF TREATMENT OF SOME SKIN DISEASES USING POTASSIUM PENETRATING SOAK AND BATH METHODS AT MEDICAL CLINIC OF THE BRIGADE 5 (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the treatment results of skin disease patients using potassium permanganate soaking and bathing.Subjects and methods: A cross-sectional descriptive study was conducted on 55 skin disease patients treated at at medical clinic of the brigade 5, from 2024 to 2025. Results: After treatment with potassium permanganate, blisters, pustules, and ulcers gradually decreased with the number of treatment days, while dry skin lesions gradually increased from 0.0% to 72.7% after 7 days of treatment. The percentage of patients experiencing unbearable pain decreased from 40.0% to 5.5% after 7 days of treatment, and the percentage of patients experiencing moderate pain also gradually decreased with treatment. The percentage of patients experiencing no pain increased significantly after treatment, from 0.0% to 47.3%. The percentage of patients experiencing severe itching and burning sensations decreased gradually over the course of treatment, from 100.0% to 9.1%. Simultaneously, the percentage of patients experiencing only mild discomfort increased from 0.0% to 41.8%, and the percentage experiencing no discomfort at all increased from 0.0% to 12.7% after 7 days of treatment.Conclusion: Potassium permanganate provides effective treatment for skin diseases, helping to reduce skin lesions and alleviate pain, itching, burning, and discomfort.
Keywords: Skin diseases, potassium permanganate soak and/or bath.